2014
DOI: 10.3109/09553002.2014.950436
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prenatal 900 MHz electromagnetic field exposures on the histology of rat kidney

Abstract: Prenatal exposure of rat kidneys to 900 MHz EMF resulted in increased total kidney volume and decreased the numbers of glomeruli. Moreover, MEL and ω-3 prevented adverse effects of EMF on the kidneys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 33 publications
1
26
0
Order By: Relevance
“…Our results based on the morphometric analysis indicated that prenatal kidney deteriorated in intrauterine life. This finding was in agreement with a previous study (11). However, the fabric was able to reduce the level of renal tissue destruction significantly.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our results based on the morphometric analysis indicated that prenatal kidney deteriorated in intrauterine life. This finding was in agreement with a previous study (11). However, the fabric was able to reduce the level of renal tissue destruction significantly.…”
Section: Discussionsupporting
confidence: 94%
“…The whole kidney was sufficiently covered by 10 slides only for each staining. The representative slides were then examined under light microscope (11). The histological evaluation involved structures including Bowman capsule, glomerular structure, basal membrane integrity, and proximal tubule basement membrane.…”
Section: Histopathological Analysismentioning
confidence: 99%
“…No significant change was found after exposure to ELF EMFs. Some studies have reported that high-frequency EMF exposure has had some harmful effects on renal morphology and function [ 31 , 32 ]. In addition, it has been reported that exposure to ELF EMFs could cause oxidative stress in kidneys [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mean numerical density and total number of purkinje cells A physical disector method was used to compute mean numerical density and total number of Purkinje cells (Ulubay et al 2015). Based on a pilot study, sections were obtained by systematic unbiased sampling.…”
Section: Stereologymentioning
confidence: 99%